iNetSec 2009 - Open Research Problems in Network Security IFIP Wg 11.4 International Workshop, Zurich, Switzerland, April 23-24, 2009, Revised Selected Papers - Camenisch, Jan; Kesdogan, Dogan (IFIP Advances in Information and Communication Technology,, 2009)
This book constitutes the refereed post conference proceedings of the IFIP WG 11.4 International Workshop, iNetSec 2009, held in Zurich, Switzerland, in April 2009. The 14 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on involving humans; Web 2.0; protecting resources; pervasive devices; protocol security; and privacy.